How to look like a dancer (without being one) - Belair, Alida 1944- (Schwartz, 2005)
Alida Belair, former prima ballerina and author of the best-selling Travel Pilates, has developed a workout for the would-be dancer in all of us - a unique fusion of classical dance, cardio, and traditional Pilates and yoga exercises. Regardless of your age, gender, shape, and size, How To Look Like a Dancer (without being one) provides an easy-to-follow workout designed to strengthen and sculpt the body, and achieve physical confidence and a dancer's poise and grace.--Book jacket.